Anticommunism and Détente: Mindszenty, the Catholic Church, and Hungarian Émigrés in West Germany, 1972. Issue 3 (September 2021) - von Klimó, Árpád
Abstract: Cardinal Mindszenty was head of the Catholic Church of Hungary between 1945 and 1974, but had been imprisoned between 1949 and 1956 and hiding in the US embassy in Budapest from 1956 to 1971. In 1971, Mindszenty left the country and settled in Vienna after long negotiations between the Vatican and the Hungarian communist government. When he visited the Hungarian diaspora and non-Hungarian followers in the West between 1972 and his death in 1975, controversies about communism, Catholicism, and Western society and social change in general erupted. This article analyzes these controversies and the different groups that supported the cardinal and their understanding of anticommunism in the context of a changing West German society and against the background of changes within the Catholic world after Vatican II. The ideas about communism Mindszenty and his right-wing supporters formulated were outdated in the 1970s but had a long afterlife.